Survival analysis and prognostic factors for prostate cancer patients at Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur - Shamsul Azhar Shah; Norzaher Ismail; Syafiq Taib; Siti Nor Mat; Nazarudin Safian (Penerbit Universiti Kebangsaan Malaysia, 2021)
Prostate cancer is the third commonest type of cancer in Malaysian men with the incidence of 1,807 in 2018 compared to 1,186 cases reported in 2014. Prostate cancer is also known to cause disease, economic burden and lead to significant financial implications for the healthcare system. This study aimed to measure the rate of survival and to determine the prognostic factors for prostate cancer patients at Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur. This was a retrospective study design involving prostate cancer patients who had been diagnosed and had sought treatment at Universiti Kebangsaan Malaysia Medical Centre from 2008 to 2017. Data were obtained from the patients’ medical records based on TRUS biopsy. The study period was from July 2017 to December 2018. Survival probabilities were estimated using Kaplan-Meier, and differences were compared using the log-rank test. The adjusted hazard ratio (HR) for variables was estimated after fitting the Cox proportion hazard model. Patients’ death status due to prostate cancer was the endpoint of the survival analysis. A total of 283 patients’ data were analysed. Total five-year and ten-year survival rates of prostate cancer patients were 77.8 and 65.5%, respectively, regardless of the stage and treatment. The predictor factors for survival age were ≥75 years (HR = 8.49, 95% C.I: 1.16-62.13), Gleason score ≥8 (HR = 2.36, 95% C.I: 1.18-4.73) and cancer metastasis complications (HR = 5.26, 95% C.I: 2.88-9.63). Survival rates and prognostic factors of prostate cancer in the study were almost similar to those in nearby countries in the region. Preventive actions such as prostate cancer screening, early detection of cancer and early treatment should be empowered to improve the survival rate of prostate cancer patients in this hospital.